ANALISIS INSTAGRAM SEBAGAI SOCIAL MEDIA MARKETING DI INDUSTRI PERHOTELAN - Elysa Nur Cahyani; Dewi Pancawati N; Endah Fitriyani (Jurnal Ilmiah Hospitality, 2021)
Social media marketing in Instagram provides an opportunity for consumers to interact better with the hotel industry, it also has greater cost effectiveness, in addition to the application, more and more unique features are emerging, making it easier for marketers to be as creative as possible. The emergence of Instagram with unique features that can be accessed around the world encourages the hotel industry to use it to market products and provides opportunities for consumers to interact better with companies so that they have higher effectiveness. The purpose of this study is to explore the reasons for the hospitality industry to use Instagram as a marketing medium as well as topics that are often researched in previous journals regarding the application of Instagram as social media marketing in the hospitality industry. The method used is qualitative with a systematic literature review approach to find relevant theories on this topic and then identified, assessed, and synthesized according to a predetermined explicit method so that the SLR approach provides clarity, transparency and impartiality as well as inclusive coverage in certain areas. The result of this research is that hotels use Instagram social media as their marketing because Instagram has many features such as hashtags and stories that can reach a broad audience. In addition, posting in image format also has a big impact on customer decisions. However, this is not the full power of Instagram marketing. On the other hand, earlier research mostly discuss aouut the application of social media marketing in hotels.